2021
DOI: 10.3389/fimmu.2021.737990
|View full text |Cite
|
Sign up to set email alerts
|

Apelin Promotes Endothelial Progenitor Cell Angiogenesis in Rheumatoid Arthritis Disease via the miR-525-5p/Angiopoietin-1 Pathway

Abstract: Angiogenesis is a critical process in the formation of new capillaries and a key participant in rheumatoid arthritis (RA) pathogenesis. The adipokine apelin (APLN) plays critical roles in several cellular functions, including angiogenesis. We report that APLN treatment of RA synovial fibroblasts (RASFs) increased angiopoietin-1 (Ang1) expression. Ang1 antibody abolished endothelial progenitor cell (EPC) tube formation and migration in conditioned medium from APLN-treated RASFs. We also found significantly high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 53 publications
(78 reference statements)
0
7
0
Order By: Relevance
“…In addition, miR‐525‐5 could regulate epithelial‐mesenchymal transition and cell proliferation in glioma by targeting Stat‐1 44 . Recently, miR‐525‐5p has been shown to be involved in EPCs angiogenesis in rheumatoid arthritis disease 45 . Our findings suggest that LINC00659 could participate in the regulation of proliferation and apoptosis of endothelial cells (HUVECs) through regulating miR‐525‐5p/Bax axis.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…In addition, miR‐525‐5 could regulate epithelial‐mesenchymal transition and cell proliferation in glioma by targeting Stat‐1 44 . Recently, miR‐525‐5p has been shown to be involved in EPCs angiogenesis in rheumatoid arthritis disease 45 . Our findings suggest that LINC00659 could participate in the regulation of proliferation and apoptosis of endothelial cells (HUVECs) through regulating miR‐525‐5p/Bax axis.…”
Section: Discussionmentioning
confidence: 66%
“… 44 Recently, miR‐525‐5p has been shown to be involved in EPCs angiogenesis in rheumatoid arthritis disease. 45 Our findings suggest that LINC00659 could participate in the regulation of proliferation and apoptosis of endothelial cells (HUVECs) through regulating miR‐525‐5p/Bax axis. However, it should be mentioned that although HUVECs are venous cell lines, they are not from deep veins (such as human saphenous vein endothelial cells).…”
Section: Discussionmentioning
confidence: 77%
“…Further biological function analysis revealed that among these 7 signal transduction pathways enriched by network pharmacology analysis, excluding the apelin signaling pathway mainly act in physiological processes such as adipogenesis, 30 angiogenesis, 31 cardiovascular functions, 32 calcium signaling pathway related to environmental information processing and energy supply and demand, 33 chemokine signaling pathway regulates immune cell trafficking, 34 TGF-β signaling pathway, AMPK signaling pathway, 35 Wnt signaling pathway 36 and p53 signaling pathway 37 is fibrosis closely related. The top 20 degree targets in PPI analysis were filtered and constructed a target-pathway network to elaborate the key signal pathway the Sch A affected in the treatment of PF among these four fibrosis-related pathways ( Figure 7D ), enriched KEGG pathway analysis of top 20 degree core targets and 4 pathways are visualized in Figure 7E , and TGF-β signaling pathway (3 targets) was the pathway with highest top 20 core targets, compared with AMPK signaling pathway (2 targets), Wnt signaling pathway (2 targets), p53 signaling pathway (1 target).…”
Section: Resultsmentioning
confidence: 99%
“…These and other results suggest hsa-miR-204 probably acts as a key molecule in the development of AS in RA and deserves further study. In addition, hsa-miR-377, hsa-miR-493, and hsa-miR-525-5p have been reported in either RA or AS ( 68 - 73 ), and whether these miRNAs take part in the other disease is also worthy of further investigation.…”
Section: Discussionmentioning
confidence: 99%